On the dipole approximation with error estimates - Boßmann, Lea; Grummt, Robert; Kolb, Martin (Letters in Mathematical Physics, 2018)
The dipole approximation is employed to describe interactions between atoms and radiation. It essentially consists of neglecting the spatial variation of the external field over the atom. Heuristically, this is justified by arguing that the wavelength is considerably larger than the atomic length scale, which holds under usual experimental conditions. We prove the dipole approximation in the limit of infinite wavelengths compared to the atomic length scale and estimate the rate of convergence. Our results include N-body Coulomb potentials and experimentally relevant electromagnetic fields such as plane waves and laser pulses.
CRIS-Team Scopus Importer:2024-10-02
Keywords: Dipole approximation; Ionization; Laser; N-body; Schrödinger operator